A Study of Customer Satisfaction at Local Physical Retail Shops in Dharan, Nepal - Pariyar, Kul Bahadur (Dristikon: A Multidisciplinary Journal, 2026)
This study was conducted to determine the effect of Product Features (PF), Price (PR), and Seller’s Service (SS) on Customer Satisfaction (CS) using a cross-sectional research design and a convenience sampling method. Primary data was collected from 281 respondents using a self-prepared five-point Likert scale questionnaire. The study proved the reliability and validity of the instruments. Data violated normality, and non-parametric tests, Spearman’s rank-order correlation, and ordinal logistic regression were applied. Both Spearman’s correlation result and the ordinal logistic regression result showed that there is a greater, significantly positive effect of the seller’s service and product features on customer satisfaction as compared to price. There was no significant effect of demographic variables age, education, and permanent residence on customer satisfaction. This study revealed that the retailers should devote more focus to product features and the seller’s services as compared to price to satisfy the customers at physical retail shops in Dharan.